Pakistan : Eighth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waivers and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report, 2004)
This paper assesses Pakistan's Eighth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and Request for Waivers and Modification of Performance Criteria (PCs). Implementation of the PRGF program in Pakistan remains broadly on track. All quantitative performance criteria for end-December 2003 were met, and it seems that most indicative targets for end-March 2004 were also met. Structural reforms are advancing, albeit only slowly in the energy sector. Four structural performance criteria were breached, but the slippages were minor and mainly reflected timing issues.